Did the A Line Arterial Bus Rapid Transit Affect Housing Values in Ramsey County, MN? - Jack Lyle Benson; Jason Cao (Findings)
As arterial bus rapid transit (BRT) has become popular in the Twin Cities, local residents worry about the housing value uplift associated with these investments and the potential displacement of poor residents. Using a before-after treatment-control design, this study developed a difference-in-difference hedonic model to examine the effects of the A Line BRT on station-area housing values. After the funding announcement and opening, housing sales prices increased slightly. However, neither effect is statistically significant. The A Line encouraged ridership but had no effect on housing values. We will explain why the Green Line light rail increased property values whereas the arterial BRT did not.